A voz da resistência negra na poesia lírica de Alzira Rufino, Beatriz Nascimento e Esmeralda Ribeiro - Nunes, Kelly Cristiane (2022)
The research presented develops an interpretative and comparative analysis of Afro-Brazilian lyric poetry composed by three black women poets: Alzira Rufino, Beatriz Nascimento and Esmeralda Ribeiro. They, like others, turn the lyrics into a weapon of resistance against the racism present in Brazilian society. In addition to racism, there are also among their ills: social inequality, misogyny and sexism. These black women fight against all these forms of oppression in their poetry. The hypothesis that guides this research is how the words of these women contribute to their freedom, about ethnic, gender and class, and the general objective is to demonstrate how black resistance is present in lyrical poetry by comparing the voices of these three Afro-Brazilian poets as way of giving voice and recognizing the importance of literature produced by black women. In order to achieve the proposed objective, we support the research on the theoretical assumptions of comparative literature with Bosi (1977) and (2002) and Coutinho (2016) and lyrical theory, we are guided by Adorno (2003), Goldstein (1989) and Cara (1985), and also on studies dealing with resistance and structural racism with Almeida (2021), Munanga (2003) and Djamila Ribeiro (2018). We observed that Afro-Brazilian literature by female authors establishes reflections from the experience of a subject crossed by the identities of being a woman and being black in Brazilian society and presents resistance in their poetics. We conclude that the poetic work carried out by these poets presents a unique historical perspective, which starts from the look of black women arranged in verses that demonstrate the strength and resistance as political acts of denunciation and fight against centuries of discrimination against the black people in Brazil. We hope this study brings contributions to the field of comparative literature and also provides theoretical support for approaching resistance in lyrical poetry